Fourteen days : [large type] a literary project of the Authors Guild of America - Atwood, Margaret, 1939-; Preston, Douglas J.; Anders, Charlie Jane; Crucet, Jennine Capó; Cassara, Joseph; Cruz, Angie; Cummings, Pat; Day, Sylvia; Donoghue, Emma, 1969-; Eggers, Dave; Gabaldon, Diana; Gerritsen, Tess; et al. (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
Set in a Lower East Side tenement in the early days of the COVID-19 lockdowns, Fourteen Days is an irresistibly propulsive collaborative novel from the Authors Guild, with an unusual twist: each character in this diverse, eccentric cast of New York neighbors has been secretly written by a different, major literary voice--from Margaret Atwood and John Grisham to Tommy Orange and Celeste Ng. One week into the COVID-19 shutdown, tenants of a Lower East Side apartment building in Manhattan have begun to gather on the rooftop and tell stories. With each passing night, more and more neighbors gather, bringing chairs and milk crates and overturned pails. Gradually the tenants--some of whom have barely spoken to each other--become real neighbors. In this Decameron-like serial novel, general editors Margaret Atwood and Douglas Preston and a star-studded list of contributors create a beautiful ode to the people who couldn't escape when the pandemic hit. A dazzling, heartwarming, and ultimately surprising narrative, Fourteen Days reveals how beneath the horrible loss and suffering, some communities managed to become stronger. Includes writing from: Charlie Jane Anders, Margaret Atwood, Jennine Capó Crucet, Joseph Cassara, Angie Cruz, Pat Cummings, Sylvia Day, Emma Donoghue, Dave Eggers, Diana Gabaldon, Tess Gerritsen, John Grisham, Maria Hinojosa, Mira Jacob, Erica Jong, CJ Lyons, Celeste Ng, Tommy Orange, Mary Pope Osborne, Douglas Preston, Alice Randall, Ishmael Reed, Roxana Robinson, Nelly Rosario, James Shapiro, Hampton Sides, R.L. Stine, Nafissa Thompson-Spires, Monique Truong, Scott Turow, Luis Alberto Urrea, Rachel Vail, Weike Wang, Caroline Randall Williams, De'Shawn Charles Winslow, and Meg Wolitzer!